The The Pluralistic Method Exploration on Mathematics Learning: A Case Study of Students with Diverse Academic Skill Levels - Mewa Zabeta; Nikmah Nurvicalesti; Ratnasari Ratnasari; Isania Marsel Viliyati (Jurnal Inovasi Matematika, 2025)
This research explored the application of the pluralistic method in mathematics learning in the classroom with students with diverse levels of academic skill. The pluralistic method is a learning approach that emphasizes the use of various methods and learning strategies tailored to the needs and characteristics of students. The subjects of this research were the students and teachers of Public JHS 01 BP Peliung, while the object of this research is the pluralistic method in mathematics learning. This study examines the application of pluralistic methods to enhance math learning among students from diverse academic backgrounds by combining qualitative and case study methods. The researchers analyzed the data through data reduction, data presentation, and conclusion drawing. This research began with observations conducted using a structured yet flexible observation guide to record classroom dynamics. The researchers then conducted semi-structured interviews with teachers and students to facilitate in-depth exploration. As the last step, the researcher made sure the data was correct by using data source triangulation techniques (observation, interviews, and documentation) and member checking. Member checking means getting confirmation from teachers or students about the research findings so the findings remain objective and free of bias during the data collection and analysis process. Finally, the researcher provided a contextual description of the conclusions. The research results show that the pluralistic method is effective in improving students' understanding of mathematical concepts, learning motivation, and academic performance. This method also has a positive impact on students' attitudes and behavior. This research has practical implications for teachers and schools in improving the quality of mathematics education.